2019
DOI: 10.1530/rep-18-0083
|View full text |Cite
|
Sign up to set email alerts
|

The quest for pluripotency: a comparative analysis across mammalian species

Abstract: Pluripotency is the developmental potential of a cell to give rise to all the cells in the three embryonic germ layers, including germline cells. Pluripotent stem cells (PSCs) can be embryonic, germ cell or somatic cell in origin and can adopt alternative states of pluripotency: naïve or primed. Although several reports have described the differentiation of PSCs to extra-embryonic lineages, such as primitive endoderm and trophectoderm, this is still debated among scientists in the field. In this review, we int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 87 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…Comparative transcriptomics will shed light on the understanding of the conservation and variations in mammalian PSCs, which share many of the criteria for pluripotency but also differ in their characteristics 13, 14, 20 . We observed that hierarchical clustering separates PSCs and fibroblasts, consistent with patterns of gene expression differences between tissues 23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparative transcriptomics will shed light on the understanding of the conservation and variations in mammalian PSCs, which share many of the criteria for pluripotency but also differ in their characteristics 13, 14, 20 . We observed that hierarchical clustering separates PSCs and fibroblasts, consistent with patterns of gene expression differences between tissues 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Derivations of PSCs from a range of species have been reported, including cow 5 , pig 6 , horse [7][8][9][10][11] , naked mole-rat 12 , and other mammalian species 13,14 . In the reprogramming of (which was not certified by peer review) is the author/funder.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCs, isolated either from embryos at different stages of pre-and early post-implantation development or from PSC lines, can be maintained in vitro applying self-renewal culture conditions [187,188] and possess cellular and molecular features that mirror different pluripotency states, defined as extended, naïve, intermediate and primed. They are characterized by distinguishable colony morphology, growth factor requirement, energetic metabolism, molecular signatures and, in the female cell lines, X inactivation status [70,189,190].…”
Section: Cellular and Molecular Features Of Stem Cell Pluripotency In Vitromentioning
confidence: 99%